PENYELESAIAN SENGKETA PERBATASAN DARAT DI SEGMEN BIDJAEL SUNAN OBEN ANTARA INDONESIA DAN TIMOR LESTE - Nadia Sabrilla (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2022)
This study aims to look into how land border disputes between Indonesia and Timor Leste along the Sunan-Oben Bidjael Segment have been settled using international law. An official editor is employed in this normative study. The study’s findings demonstrate that a Joint Border Committee between Timor Leste and Indonesia has been established to serve as a forum for settling land border disputes. Later, This team then changed its name to The Treaty of 1904 and the Permanent Court of Arbitration of 1914 (PCA 1914) have been chosen by the Technical Sub-Committee on Boundary Demarcation and Regulation (TSC-BDR) as the border demarcation legal framework. Article 8 of the 2005 Provisional Agreement states that local communities, in this case indigenous peoples and traditional leaders at the borders, are given the opportunity to participate in the dispute resolution procedure that takes place on the border between the two countries by promoting nonviolent and peaceful means. (b). It is evident that the systems of customary law that apply to the residents of East Timor (Timor Leste) and West Timor (Indonesia) are the same given that these two communities share a shared sociocultural background. Land conflicts, the boundaries of a community’s territory, and the ability of community leaders to engage in direct discussions to resolve these issues can all be governed by the basic principles of customary law.